2017
DOI: 10.1128/genomea.00203-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of a Multidrug-Resistant Pseudomonas aeruginosa Strain Isolated from a Patient with a Urinary Tract Infection in Khartoum, Sudan

Abstract: Pseudomonas aeruginosa infection is difficult to treat due to the presence of antibiotic resistance determinants. Here, we report the genome sequence of a multidrug-resistant P. aeruginosa strain isolated from a patient with a urinary tract infection in 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The study showed that 74 of the isolates were resistant to carbenicillin [31]. While a new study conducted in Sudan found a multidrugresistant (MDR) P. aeruginosa isolate from urine of patient with a urinary tract infection was highly resistant to many antibiotics including ciprofloxacin, gentamicin, ceftazidime, piperacillin, and meropenem [32].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that 74 of the isolates were resistant to carbenicillin [31]. While a new study conducted in Sudan found a multidrugresistant (MDR) P. aeruginosa isolate from urine of patient with a urinary tract infection was highly resistant to many antibiotics including ciprofloxacin, gentamicin, ceftazidime, piperacillin, and meropenem [32].…”
Section: Discussionmentioning
confidence: 99%
“…This was further confirmed following the genomic analysis of the resistance genes (Table 2). Several published studies on P. aeruginosa genome characterization have highlighted the prevalence of blaPAO and blaOXA50 which are classified as β-lactamases resistance genes [44,45]; and this does not make a difference in the P. aeruginosa strains under study. In the study conducted by Girlich and colleagues [32], it was confirmed that insertion of blaOXA-50 into a P. aeruginosa host, decreases susceptibility to ampicillin, ticarcillin, moxalactam and meropenem.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Apart from the rmtB gene, aminoglycosides modifying enzymes (AMEs) were found within UY1PASBAL and UY1PSABAL2 genomes, and it was exclusively aminoglycoses phosphotransferases (APHs) that mostly confer resistance to amikacin and isepamicin [49]. The aph(3')-IIb variant found in both UY1PASBAL and UY1PSABAL2 genome has been observed among MDR P. aeruginosa from several studies [44,45,50].…”
Section: Plos Onementioning
confidence: 99%
“…Pseudomonas aeruginosa is an opportunistic Gram-negative, rod-shaped bacterium that is frequently implicated in community-acquired and nosocomial infections [1]. It has a natural resistance to different classes of antimicrobial agents, along with the ability to acquire resistance to all other treatment choices [2].…”
Section: Introductionmentioning
confidence: 99%